Identifikasi Drug Related Problems (Drps) Potensial Pada Pasien Asma Di Instalasi Rawat Inap Rsud Dr. Moewardi Tahun 2015 - Pangastuti, Restu Bunga, Dra. Nurul Mutmainah, M.Si., Apt (2017)
Asthma is a public health problem in almost all countries in the world. Potential drug related problems (DRPs) contribute to morbidity and mortality in asthmatic atients. This study aims to determine the incidence of Drug Related Problems (DRPs) with category of wrong drug selection that includes the use of ineffective drugs, the use of unsafe drugs, and the use of drug combination that are not necessary in asthmatic patients in Dr. Moewardi Surakarta Hospital in 2015. This research was conducted with non-experimental descriptive design and data acquisition retrospectively for medical record data. Samples were collected with purposive sampling method. The patient's criteria as subject in this study were diagnosed with asthma, receive asthma medication, receive more than 2 medications, and have complete medical data record. Samples were analyzed to identify drug interactions based on the literature Stockley's Drug Interaction 2008 and drug interaction checker (www.drugs.com and www.medscape.com). Global initiative for asthma 2011 and Drug Information Handbook 2009 are used to identify wrong drug selection. The data were analyzed descriptively. Out of the 59 samples, the result showed there were 40 patients (67.79%) with wrong drug selection that includes 2 cases (2,59%) were the use of ineffective drugs, 61 cases (82,44%) were the use of unsafe drugs, and 11 cases (14,86%) were the use of drug combination that are not necessary. The incidence of potential drug interactions occured in 48 patients (81,35%) with 216 cases drug interactions.